Percutaneous endoscopic gastrostomy for nutrition in patients with oesophageal cancer - Stockeld, Dag; Fagerberg, Jan; Granström, Lars; Backman, Lars (The European journal of surgery, 2001)
Objective: To evaluate the technical aspects and risks of using percutaneous endoscopic gastrostomy (PEG) in the treatment of patients with oesophageal cancer. Design: Retrospective study. Setting: Teaching hospital, Sweden. Subjects: 229 consecutive patients who presented with oesophageal cancer between January 1990 and the end of December 1999. Intervention: Insertion of a PEG after diagnosis and before treatment. Main outcome measures: Morbidity and mortality. Results: PEGs were successfully inserted in 222/229 (97%), and the tumour required dilatation in 103 (45%). There was 1 oesophageal perforation and 1 tear of the stomach wall, both of which resulted in death (mortality 0.9%). In 1 operated patient the right gastroepiploic artery was injured by the PEG, but this did not prevent the stomach being used successfully as the oesophageal substitute. PEGs were removed because of leaks in 2 patients. There was 1 possible implantation metastasis. Conclusion: PEG is a safe and a well tolerated way of ensuring enteral nutrition in patients with oesophageal cancer. The risk of the PEG complicating any later operation is minimal. Copyright © 2001 Taylor and Francis Ltd.